The Spatial Composition of Beach Litter in North Central Timor Regency, East Nusa Tenggara Province, Indonesia - Rizki Bonbalan; Lumban Nauli Lumban Toruan; Ismawan Tallo; Suprabadevi Ayumayasari Saraswati (Jurnal Kelautan, 2022)
ABSTRACTMarine litter is currently an environmental problem that has become a global issue and attracts everyone's attention because it has a significant negative impact on the marine and coastal environment. One of the concerns at this time is the amount of marine litter in coastal areas. The purpose of this study is to determine the type and composition of waste on the beach. This study was conducted on nine coastal beaches of the North Central Timor Regency in August 2020. The sampling technique was used by adapting the Guidelines on Survey and Monitoring of Litter method. Sampling was carried out by drawing a line 100 m long parallel to the coast and a transect width of 10 m from land to sea with sampling boundaries, namely dunes, vegetation and anthropogenic activities. The results of the study show that the composition of plastic waste is 79,7%, paper and cardboard 3,5%, foam and cork 2,7%, cloth 1,8%, glass and ceramics 1,6%, rubber 2,6%, wood 1,9%, metal 1%, and others 5,3%. The category of litter that dominates the entire study beach is plastic.Keywords: Beach, litter, plastic, North Central Timor Regency, Timor Leste